Making A Web-Based Visual Novel Game To Introduce The Library Of UNIKA Soegijapranata - Alvin L.K, Alfonsus; Harnadi, Bernardus; P, FX Hendra (Journal of Business and Technology, 2024)
As technology develops, its impact can be felt in human daily life. One of the aspects affected by the development of technology is the library. The library must be able to show that the library can also adapt as technology evolves. Of course this also applies to the library of Unika Soegijapranata, the game "mengenal perpustakaan" will help players get to know and learn about the facilities owned by the library of Unika Soegijapranata. The purpose of this research is to design and create a game that introduces the Unika library that is also interesting to play. This game is intended for the general public. So the planned game is going to be a web-based Visual Novel game using Ren'Py using various assets that are royalty free. For the surveys. The total subjects were 34 people, most of them were 22-24 years old. For the results of the survey, the results were valid and reliable. The correlation result says that Enjoyment and Effort Expectancy have a high correlation on Behavior Intention, while Performance Expectancy has a moderate correlation. The end result of this research is a visual novel game where players can read and answer quizzes about the library of Unika and the various facilities owned by them. To make the game interesting there are quizzes for each floor.